2000
DOI: 10.1046/j.1460-9568.2000.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Amyloid neurotoxicity is mediated by a glutamate‐triggered excitotoxic cascade in rat nucleus basalis

Abstract: β-Amyloid neurotoxicity is mediated by a glutamate-triggered excitotoxic cascade in rat nucleus basalis Harkany, T.; Ábrahám, I.; Timmerman, W.; Laskay, G.; Tóth, B.; Sasvári, M.; Kónya, C.; Sebens, J.B.; Korf, Jakob; Nyakas, C. Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Harkany, T., Ábrahám, I., Timmerman, W., Laskay, G., Tóth, B., Sasvári, M., ... Luiten, P. G. M. (2000). β-Amyloid neurotoxicity is mediated by a glutamate-triggered excitotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(164 citation statements)
references
References 66 publications
7
154
0
3
Order By: Relevance
“…It is thus of great interest to elucidate the physiological role of Ah under normal conditions. At present, the physiological role of Ah is not clear, but suggestions include a neurotrophic action at a low concentration (Chauhan et al, 1991), enhancement of N-methyl-D-aspartate (NMDA) receptormediated current (Furukawa and Mattson, 1998;Harkany et al, 2000) and long-term potentiation (Ishida et al, 1997), enhancement of AMPA receptor-mediated current (Blanchard et al, 1997), formation of calcium channels (Bhatia et al, 2000), and effects on intracellular calcium homeostasis (Bhatia et al, 2000;Mattson et al, 1993). Most of these suggestions need to be confirmed, and it is not clear whether the suggested actions of Ah can be mediated by physiological concentrations of Ah.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus of great interest to elucidate the physiological role of Ah under normal conditions. At present, the physiological role of Ah is not clear, but suggestions include a neurotrophic action at a low concentration (Chauhan et al, 1991), enhancement of N-methyl-D-aspartate (NMDA) receptormediated current (Furukawa and Mattson, 1998;Harkany et al, 2000) and long-term potentiation (Ishida et al, 1997), enhancement of AMPA receptor-mediated current (Blanchard et al, 1997), formation of calcium channels (Bhatia et al, 2000), and effects on intracellular calcium homeostasis (Bhatia et al, 2000;Mattson et al, 1993). Most of these suggestions need to be confirmed, and it is not clear whether the suggested actions of Ah can be mediated by physiological concentrations of Ah.…”
Section: Discussionmentioning
confidence: 99%
“…3) (Gaykema et al, 1992). Cholinergic neurons and fibers were visualized with the cholinergic marker choline-acetyl transferase (ChAT, EC3.2.1.6) (Harkany et al, 2000). The fiber density was measured in the superficial sublayer of the layer V as described earlier (Horváth et al, 2000).…”
Section: Calpain Inhibition Prevents Ab-induced Degeneration Of Cholimentioning
confidence: 99%
“…A number of studies suggest that Ab-induced toxicity in AD is caused by excessive glutamate stimulation, over activation of the NMDA receptor, and subsequent calcium accumulation in the postsynaptic neuron (Harkany et al, 2000;Molnár et al, 2004;Mattson et al, 2000). Recently, the pathology of Ab has been correlated to oligomeric forms of the peptide (for review see Walsh and Selkoe, 2007), and studies indicate an involvement of the NMDA receptor also in oligomer toxicity (Shankar et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3][4][5][6] have shown the benefits of early diagnosis and treatment, according to Dr. Small. Early, accurate diagnosis and treatment maintained patients at a higher level of functioning, leading to fewer doctor and hospital visits compared with patients who were not treated early.…”
Section: Innovations Affecting Study Designmentioning
confidence: 99%
“…3 Reduced caregiver burden 3,4 and delay in nursing home placement 5 can also result from early treatment of Alzheimer's disease, as can reduced use of other psychotropic drugs. 6 …”
Section: Innovations Affecting Study Designmentioning
confidence: 99%